Analisis profitabilitas bank syariah indonesia (BSI) tahun 2020–2024 menggunakan pendekatan return on equity (ROE) - Saputra, Lubbul Hikam; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This research looks into how Bank Syariah Indonesia (BSI)’s profitability has grown from 2020 to 2024, focusing on the Return on Equity (ROE) ratio. We picked ROE as the main measure since it shows how well the bank turns shareholders’ equity into net profits, which is a key sign of how effectively management handles things. We’re using a descriptive quantitative method, pulling secondary data from BSI’s annual reports over those years. What we found is a steady rise in BSI’s ROE: starting at 11.18% in 2020, jumping to 13.71% in 2021, then up to 16.84% in 2022, holding at 16.88% in 2023, and hitting 17.77% by 2024. This climb points to better bank management in making the most of capital for profits. Our results match up with earlier studies that say Islamic bank profitability depends on things like solid financing, smooth operations, and strong asset quality. Hopefully, this can give useful info to academics, regulators, and folks in the Islamic banking world about how profitability is doing in Indonesia.